Mosque in Compact Cities: Impact of Urbanization on Planning and Design of Contemporary Mosques in Nusantara - Sarram, Arman; Utaberta, Nangkula; Asif, Nayeem (International Journal of Engineering and Technology, 2019)
Thousands of years after the creation of Islamâ€™s place of worship, issues and problems of its continuous establishment stemming from complexity of modern living has forced urban planners and architecture to reconsider its planning and implementation, deviating from the usual architectural conventions and faced with the challenge of retaining the integrity of its fundamental functionality, purpose and appropriateness. This paper provides insight on the merits as well as the challenges of modern day planning, executing and building of mosque in urban areas by providing a comparative analysis on several mosques from different cities around the world. The paper adopts qualitative approach towards collecting and analyzing the data which primarily comes from review of literature. Outcome of this researchâ€™s showed that a strong consideration for vertical development should be implemented to serve the needs of a growing population and fast dwindling resources and space. Additionally, results also found that vertical development and practical space usage in harmony with aesthetics and environment to achieve balance of both use and presentation.Â Â